Предмет: Алгебра,
автор: Hizako
Как решить? Объясните пожалуйста
2-n/3-m + n+2/m-3
Ответы
Автор ответа:
0
Решение
(2 - n)/(3 - m) + (n + 2)/(m - 3) = (2 - n)/(3 - m) - (n + 2)/(3 - m) = (2+ n -2)/(3 - m) =
= n/(3 - m) = -2/(m -3 )
(2 - n)/(3 - m) + (n + 2)/(m - 3) = (2 - n)/(3 - m) - (n + 2)/(3 - m) = (2+ n -2)/(3 - m) =
= n/(3 - m) = -2/(m -3 )
Похожие вопросы
Предмет: Химия,
автор: saradauchiha24
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Дануськин